Sunday, 14 July 2013

elementary number theory - How is induction used to prove that gcd(an,bn)=|n|gcd(a,b)



In the book Elementary Number Theory: Primes, Congruences and Secrets written by William Stein, which can be found at http://wstein.org/ent/, Stein proves the following at page 6/lemma 1.1.17:




Lemma   For any integers a,b,n, we have gcd(an,bn)=|n|gcd(a,b)



Proof   We step through Euclid's algorithm for gcd(an,bn) and note

that at every step the equation is the equation from Euclid's
algorithm for gcd(a,b) but multiplied through by n. For simplicity,
assume that both a and b are positive. We will prove the lemma by
induction on a+b. The statement is true in the base case when a+b2, since then a=b=1. Now assume a,b are arbitrary with ab.
Let q and r be such that a=bq+r and 0r<b. Then by Lemmas
1.1.9-1.1.10, we have gcd(a,b)=gcd(b,r). Multiplying a=bq+r by n we see
that an=bnq+rn, so gcd(an,bn)=gcd(bn,rn). Then



b+r=b+(abq)=ab(q1)a<a+b,




so by induction gcd(bn,rn)=|n|gcd(b,r). Since gcd(b,r)=gcd(a,b), this proves the lemma.




My main question concerning this proof is that i have troubles following how b+r<a+b leads to the fact that gcd(bn,rn)=|n|gcd(b,r).



I think that my troubles comprehending this proof is related to my basic understanding of mathematical induction, I never even knew what it was before stumbling upon this proof. My current understanding of induction is that you prove your statement for a base case, a+b=2, then you prove that if the statement is true for any one natural number then it is true for the next. However i do not understand how that principle is used in this proof, any explanation is greatly appriciated.


Answer



You are correct that mathematical induction consists of three steps:





  1. Prove the base case.

  2. Assume that the claim is true for some nN (possibly including 0 if needed).

  3. Use the above assumption to prove the claim for n+1.



Let us see this in practice with standard example:



1+2+3++n=n(n+1)2




Base case: 1=1(1+1)2(obviously true)



Assume that formula (1) is true for some n. Now we need to prove that 1+2+3++nuse the assumption on this+(n+1)=(n+1)(n+2)2

and we can use the assumption to get 1+2+3++n+(n+1)=n(n+1)2+(n+1)=(n+1)(n+2)2
so we are done.



Now, in your example, what is used is version of induction called strong induction. The difference is that in step 2, we assume something stronger, but it turns out this is equivalent to "weak" induction (just happens to be more convenient in some cases).




  1. Prove the base case.

  2. Fix some nN and assume that the claim is true for all natural numbers k when k<n.

  3. Use the above assumption to prove the claim for n.







I will now try to clarify the steps in your proof. Let us define m=a+bN. We will do induction on m.



Base case is m=2. Since a+b=2 and a,b>0, we must have a=b=1, so gcd(na,nb)=gcd(n,n)=|n|=|n|gcd(a,b).



Now let mN and assume that gcd(na,nb)=|n|gcd(a,b),(a,bN) a+b<m.

We want to prove that the claim is true for a,b (remember that a+b=m).




Using Euclid's division, we have a=qb+r, $0\leq |r|

Notice that if we can prove that gcd(nb,nr)=|n|gcd(b,r),

we will have gcd(na,nb)=|n|gcd(a,b)
as well. So let us see if we can employ our assumption (2) - for it to work, we must check that $b+r

Also, notice that we indeed needed strong induction, since we don't know that b+r+1=m, which we would want in ordinary induction.


No comments:

Post a Comment

real analysis - How to find limhrightarrow0fracsin(ha)h

How to find limh0sin(ha)h without lhopital rule? I know when I use lhopital I easy get $$ \lim_{h\rightarrow 0}...